Socio-Demographic relationship with the prevalence of dental caries and fissure sealants in Pediatric Patients at the Dental Hospital Department of Pediatric Dentistry Baiturrahmah University - Sri P. Utami; Niatul Umami (DiscoverSys Inc., 2022)
Objective: The aim of this study was to assess the prevalence of dental caries and the DMFT index as well as the distribution pattern of pits and fissure sealants in permanent teeth, to estimate whether sealant use and socio-demographic factors correlate with caries prevalence in the sample examined in pediatric patients at the Dental Hospital Department of Pediatric Dentistry Baiturrahmah University. Material and Methods: This type of research is quantitative with analytic descriptive method with cross sectional research design. The population was pediatric patients who visited the Dental Hospital Department of Pediatric Dentistry Baiturrahmah University in July 2020. Sampling in this study used the total sampling method, which means that all members of the population were sampled. Results: The results of the study were divided into 2 categories, namely socio-demographic and oral health behavior. This category is obtained from the results of the hypothesis in each category. Especially in the category of oral health behavior, the overall result of the hypothesis is smaller than 0.05. Conclusion: This hypothesis shows that there is a relationship (correlation) between dental health behavior with the prevalence of dental caries and fissure sealants in pediatric patients in the Dental Hospital Department of Pediatric Dentistry Baiturrahmah University.